Challenges of PARFOR program: construction of meanings in the pedagogy course (Revista Internacional de Formação de Professores, 2019)
That is a research in a Pedagogy course sponsored by the National Plan for Elementary Education Teacher Training (PARFOR Program). Before the necessity to offer initial formation for individuals who have already had knowledge from teacher experience, the course adopted integrated thematic projects methodology in the interdisciplinary approach. Aiming to understand how projects provided construction of meanings during the formation, this paper discusses the Brazilian scenery of transformations of Pedagogy courses since the 1990s; presents the methodological procedures; concludes reflecting that it was important to overcome a strict curricular conception, in order to integrate theory and practice.
Keywords: Pedagogy Course. PARFOR Program. Integrated thematic projects.